Factors Affecting Infrastructure, Utilities, And Transportation Stock Price - Annas, Mohammad; Humairoh, Humairoh (Publisher Cv. Inara, 2023)
The aim of the study was to define the performance of the blue-chips stock price listed at The Indonesia Stock Exchange in particular the stock price of the establishments which organize the energy sectors, infrastructure and transportations. The reason of choosing those particular establishments was due to its fluctuate and price correction frequently. The analysis was done by distributing the related research variables and endorsed the hypothetical factors. The chosen factors then being simulated with statistical analysis instruments. The independent variables such as the inflation rates, interest rates and private investments were simulated to have particular correlation and affecting rate toward the stock price. The findings showed that fundamental variables had no effect on the stock prices of the infrastructure, utilities, and transportation sectors.